Risk factors analysis of 90-day mortality in patients with sepsis in intensive care unit. - Yuntian Xu; He Zhang; Jiezhi Li; Nan Wang; Huifeng Yuan (PLoS ONE, 2025)
Background The incidence and mortality of sepsis in the intensive care unit (ICU) remain persistently high. This study primarily investigates the risk factors associated with the 90-day mortality in sepsis patients. Method This retrospective study included 123 sepsis patients admitted to a hospital in China from January 2015 to December 2018, clinical and abdominal CT data were compared between survivors and non-survivors, logistic regression and Cox regression analyses were performed on the abdominal CT data, Finally, survival curves for different skeletal muscle indices were analyzed using the Kaplan-Meier (K-M) method. Result In the abdominal CT scan data, significant differences were observed between survivors and non-survivors in skeletal muscle density (SMD), skeletal muscle area (SMA), skeletal muscle index (SMI), and subcutaneous adipose tissue area (SAT); Cox regression analysis revealed that higher skeletal muscle density (SMD) (HR = 0.953; 95% CI = 0.923-0.984; p = 0.003), skeletal muscle area (SMA) (HR = 0.986; 95% CI = 0.976-0.997; p = 0.011), and skeletal muscle index (SMI) (HR = 0.951; 95% CI = 0.917-0.985; p = 0.005) were significantly associated with lower 90-day mortality compared to non-survivors. Finally, the Kaplan-Meier (K-M) curves demonstrated differences in survival based on the median skeletal muscle index (SMI). Conclusion Body composition parameters assessed by abdominal CT scans are highly associated with 90-day mortality in ICU patients with sepsis. Among them, SMD, SMA, and SMI are valuable prognostic factors.